2021
DOI: 10.3390/md19030133
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide from Porphyridium cruentum (purpureum) is Not Toxic and Stimulates Immune Response against Vibriosis: The Assessment Using Zebrafish and White Shrimp Litopenaeus vannamei

Abstract: Exopolysaccharides, or extracellular polysaccharides (EPS, sPS), represent a valuable metabolite compound synthesized from red microalgae. It is a non-toxic natural agent and can be applied as an immunostimulant. The toxicity test of exopolysaccharides from Porphyridium has been done in vivo using zebrafish (Danio rerio) embryonic model, or the ZET (zebrafish embryotoxicity test). The administration of extracellular polysaccharides or exopolysaccharides (EPS) from microalgae Porphyridium cruentum (synonym: P. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Granular cells and semi-granular cells exert cytotoxicity and activate the prophenoloxidase system (PO system), but hyaline cells do not activate the PO system. Phagocytosis and respiratory burst (production of superoxide anions) are the major immune abilities of hyaline cells [25]. We found that the LAB feed markedly increased the number of granular cells (Figure 1B) and semi-granular cells (Figure 1C) after 8 weeks of administration.…”
Section: Investigation For Immunity Indexmentioning
confidence: 71%
“…Granular cells and semi-granular cells exert cytotoxicity and activate the prophenoloxidase system (PO system), but hyaline cells do not activate the PO system. Phagocytosis and respiratory burst (production of superoxide anions) are the major immune abilities of hyaline cells [25]. We found that the LAB feed markedly increased the number of granular cells (Figure 1B) and semi-granular cells (Figure 1C) after 8 weeks of administration.…”
Section: Investigation For Immunity Indexmentioning
confidence: 71%
“…The difference in THC values in each treatment may be due to the various concentrations of active ingredients in food due to the treatment that has been determined. The low value of THC at P1 (control) may be influenced by physiological factors such as the slow formation of hemocytes in the shrimp body [ 47 , 48 ]. The exciting discussion confirmed that the low number of shrimp hemocytes is due to infiltration of regenerated tissue and hemocyte cell death due to apoptosis [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FCR value in both ponds was considered good. The good FCR value in shrimp culture is 1.37-1.66 [3]. The FCR value indicates the level of performance of shrimp in converting feed to yields.…”
Section: Feed Conversion Ratio (Fcr)mentioning
confidence: 99%
“…The advantages comprised the fry quality of shrimp are easy to obtain, having high survival rate, can be cultivated in ponds with high stocking densities, more resistant to disease, short cultivation cycle, and has low feed conversion [2]. The species has become an object for studies to increase their immune system against vibriosis [3].…”
Section: Introduction mentioning
confidence: 99%